Computer Vision : Identifikasi Umur Ikan Koi Berbasis Android - Hasan, Yasir (MEANS (Media Informasi Analisa dan Sistem), 2020)
Koi fish have a long life of more than 200 years, but in general Koi fish are currently around 50 to 70 years, this is due to inadequate facilities and lack of knowledge in Koi fish care. The age of koi fish can be known in several ways, such as knowing by looking at the annual signs or called Annulus and a daily called Circulus. This method is done by observing certain body parts in Koi fish. However, this method is not appropriate at this time and only people who have special expertise can know the age of koi fish. Utilization of computer technology can be used to determine the age of koi fish. The right technology that can be used is computer vision by utilizing a camera on a handheld computer device. In addition, the method that can be used is to process knowledge data on koi fish in the form of long frequencies or size distances. Better size distance in image processing is the Euclidean Distance method. Utilization of this applied technology to determine the age of koi fish is done by measuring the distance of the points specified on the koi fish object as the length of the koi fish. Of course, to do this the system must be equipped with knowledge about the size of koi fish in real terms.